Managerial accounting : manufacturing and service applications - Schneider, Arnold, 1953-; Sollenberger, Harold M. (Cincinnati, Ohio : Dame Thomson Learning, 2000)
This book is divided into five parts: Managerial accounting framework; Product cost framework; Planning and control framework; Decision-making framework; and Extension in managerial analysis.
Keywords: Accounting; Managerial accounting; Cost accounting